Tubular Cell Glucose Metabolism Shift During Acute and Chronic Injuries - Faivre, Anna; Verissimo, Thomas; Auwerx, Hannah; Legouis, David; de Seigneux, Sophie (Frontiers in Medicine, 2021)
Acute and chronic kidney disease are responsible for large healthcare costs worldwide. During injury, kidney metabolism undergoes profound modifications in order to adapt to oxygen and nutrient shortage. Several studies highlighted recently the importance of these metabolic adaptations in acute as well as in chronic phases of renal disease, with a potential deleterious effect on fibrosis progression. Until recently, glucose metabolism in the kidney has been poorly studied, even though the kidney has the capacity to use and produce glucose, depending on the segment of the nephron. During physiology, renal proximal tubular cells use the beta-oxidation of fatty acid to generate large amounts of energy, and can also produce glucose through gluconeogenesis. In acute kidney injury, proximal tubular cells metabolism undergo metabolic adaptations, shifting away from beta-oxidation of fatty acids and gluconeogenesis towards glycolysis. In chronic kidney disease, the loss of fatty acid oxidation is also well described, and data about glucose metabolism are emerging. We here review the modifications of proximal tubular cells glucose metabolism during acute and chronic kidney disease and their potential consequences, as well as the potential therapeutic implications.